Immune-Related Functions of the Hivep Gene Family in East African Cichlid Fishes - Diepeveen, Eveline T. (Genetics Society of America, 2013)
Immune-related genes are often characterized by adaptive protein evolution. Selection on immune genes can be particularly strong when hosts encounter novel parasites, for instance, after the colonization of a new habitat or upon the exploitation of vacant ecological niches in an adaptive radiation. We examined a set of new candidate immune genes in East African cichlid fishes. More specifically, we studied the signatures of selection in five paralogs of the human immunodeficiency virus type I enhancer-binding protein (Hivep) gene family, tested their involvement in the immune defense, and related our results to explosive speciation and adaptive radiation events in cichlids. We found signatures of long-term positive selection in four Hivep paralogs and lineage-specific positive selection in Hivep3b in two radiating cichlid lineages. Exposure of the cichlid Astatotilapia burtoni to a vaccination with Vibrio anguillarum bacteria resulted in a positive correlation between immune response parameters and expression levels of three Hivep loci. This work provides the first evidence for a role of Hivep paralogs in teleost immune defense and links the signatures of positive selection to host–pathogen interactions within an adaptive radiation.